2018
DOI: 10.1155/2018/4918757
|View full text |Cite
|
Sign up to set email alerts
|

CardioMEMS in a Busy Cardiology Practice: Less than Optimal Implementation of a Valuable Tool to Reduce Heart Failure Readmissions

Abstract: Introduction Congestive heart failure is a leading cause of cardiovascular morbidity and mortality that results in a significant financial burden on healthcare expenditure. Though various strategies have been employed to reduce hospital readmissions, one valuable tool that remains greatly underutilized is the CardioMEMS (Abbott), a remote pulmonary artery pressure-monitoring system, which has been shown to help reduce heart failure rehospitalizations in the CHAMPION (CardioMEMS Heart Sensor Allows Monitoring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Among its advantages, it allows trustworthy and automatic measurements. Compared with the CardioMEMS implant [43,44], this subcutaneous implant is less invasive, and once the gateway is installed, data transmission will not require any commitment (a priori) on the part of the patient. It is already known that adherence to self-care is an important issue in the field of chronic conditions [45], including heart failure [46][47][48].…”
Section: Pros and Cons Of An Implantable Monitoring Devicementioning
confidence: 99%
“…Among its advantages, it allows trustworthy and automatic measurements. Compared with the CardioMEMS implant [43,44], this subcutaneous implant is less invasive, and once the gateway is installed, data transmission will not require any commitment (a priori) on the part of the patient. It is already known that adherence to self-care is an important issue in the field of chronic conditions [45], including heart failure [46][47][48].…”
Section: Pros and Cons Of An Implantable Monitoring Devicementioning
confidence: 99%
“…Singh et al . 23 showed, before the COVID-19 pandemic invaded us, that despite its well-established beneficial clinical outcomes in the management of HF patients, adoption of CardioMEMS was slow and among their patient population only 21% of patients eligible for the device received it.…”
Section: Haemodynamic Monitoring Using Cardiomemsmentioning
confidence: 99%
“…While invasive solutions such as cardioMEMS have already demonstrated to decrease HF patients' hospitalization ( 6 ), their utilization has been limited mainly due to invasiveness and related adverse events ( 7 ) or lack of penetrance among medical doctors ( 8 ). The spectrum of non-invasive telemedicine is, instead, broad, and the recent positive results achieved by Köhler et al ( 9 ) and confirmed by the meta-analysis of Zhu et al ( 10 ) are encouraging.…”
Section: Opinion Lettermentioning
confidence: 99%